EFFECT OF KATUK LEAVES MEAL (Sauropus Androgynus L. Merr) AND ZN BIOCOMPLEX SUPPLEMENTATION ON CONSUMPTION AND DIGESTIBILITY OF POSTWEANING MALE OF ETTAWA CROSSBRED - Yakob Robert Noach; Marthen Yunus (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
The experiment goal was to determine the supplementation effect of katuk leaves meal and Zn bio complex on dry and organic matter consumption and digestibility of postweaning male of Ettawa Crossbred. The experiment used sixteen heads of the postweaning male of Ettawa Crossbred aged 4-5 months with an initial body weight of 9.01±1.85kg (CV 20.55%). Completely Block Randomized Design (CBRD) with 4 treatments and 4 replications were applied in this experiment. Those treatments were P0: Lamtoro + concentrate without katuk leaves meal and Zn biocomplex (control); P1: P0 + 5% katuk leaves meal (on the basis of forage dry matter) and Zn bio complex; P2: P0 + 10% katuk leaves meal (on the basis of forrage dry matter) and Zn bio complex; P3: P0 + 15% katuk leaves meal (on the basis of forage dry matter) and Zn bio complex. Variables measured were dry matter (DM) consumption, organic matter (OM) consumption, DM digestibility, and OM digestibility. Average of DM consumption were P0 (326.68 ±44.13g/h/d), P1 (351.68±63.47g/h/d), P2 (351.78±33.41g/h/d) and P3 (346.24±32.48g/h/d). Average of OM consumption were, P0 (300.38 ±41.14g/h/d), P1 (316.11±57.05g/h/d), P2 (315.54±30.83g/h/d) and P3 (309.21±29.00g/h/d). Average of DM digestibility, P0 (78.94 ±4.67%), P1 (78.77±9.54%), P2 (64.82±11.45%), P3 (75.38±14.56%). Average of OM digestibility, P0 (81.17±4.01%), P1 (80.77±8.69%), P2 (68.79±9.90%), and P3 (76.93±12.77%). The result of variance analysis showed that treatment has a significant effect (P<0.05) on dry and organic matter consumption but no significant (P>0.05) on dry and organic matter digestibility It can be concluded that supplementation of of katuk leaf meal (Sauropus androgynus L. Merr) at 5% up to 15% and Zn bio complex might increase dry and organic matter consumption of postweaning male of Ettawa crossbred.